An Analysis of the Application of Computer-based Multimodal Discourse Analysis in English Teaching Reform. Issue 3 (October 2020) - Zhou, Shiqing
Abstract: Metaphor is ubiquitous in people's daily life. Color is a cognitive way of human beings to the outside world. When we use the basic category of color to express other cognitive domains, we form the cognitive metaphor of color. Due to the common cognitive characteristics, the English and Chinese nationalities have a certain degree of similarity in the recognition of color words. However, influenced by various external factors, their recognition of color words shows their own unique personality. By comparing the conceptual metaphors of color idioms between English and Chinese, this paper reveals the similarities and differences between the metaphors of Chinese and English color words in a language environment close to nature, and finds out the characteristics of the metaphors of color words. The development of computer technology provides us with the possibility of analyzing specific problems. This article analyzes the application of computer-based multimodal discourse analysis in English teaching reform.